Enhancing energy yield and reducing environmental impact through co-hydrothermal carbonization of undehydrated sewage sludge and fungus bran - Guo, Shuai (2024)
This study presents a sustainable waste management method through co-hydrothermal carbonization (Co-HTC) of undehydrated sewage sludge (SS) and fungus bran (FB), effectively eliminating the need for additional water. The effects of the reaction severity factor (SF: 0.1, 0.2, and 0.3), the FB mixed ratio (FBMR: 0 %, 10 %, and 20 %), and the proportion of citric acid promoting agent (CAPA: 0 %, 10 %, and 20 %) on HTC performance were systematically investigated. The process was optimized for maximum energy yield (EY) using response surface methodology (RSM). The properties of the produced hydrochar, along with its EY and environmental impact, were thoroughly assessed. Results demonstrated that under optimal conditions (SF: 0.1, FBMR: 20 %, and CAPA: 20 %), EY increased by 45.84 % compared to hydrochar derived from dried SS. The dehydration and decarboxylation processes led to lower H/C and O/C ratios, producing hydrochar with reduced sulfur and nitrogen content, while the contents of alkali and alkaline earth metals, particularly calcium, increased. Furthermore, the optimized Co-HTC process had minimal environmental impact. In contrast to traditional HTC, which requires significant freshwater and involves high costs for SS drying, our innovative approach using undehydrated SS offers a cost-effective and environmentally friendly solution, paving the way for industrial-scale Co-HTC and sustainable waste valorization.